Respuesta :

Since

[tex]n!=\Gamma(n+1)=\displaystyle\int_0^\infty t^ne^{-t}\,\mathrm dt[/tex]

you have

[tex]\left(\dfrac12\right)!=\displaystyle\int_0^\infty t^{1/2}e^{-t}\,\mathrm dt[/tex]

Let [tex]u=t^{1/2}[/tex], so that [tex]u^2=t[/tex] and [tex]2u\,\mathrm du=\mathrm dt[/tex]. This means the integral is equivalent to

[tex]\displaystyle2\int_0^\infty u^2e^{-u^2}\,\mathrm du[/tex]

Integrating by parts, setting [tex]f=u[/tex], [tex]\mathrm df=\mathrm du[/tex] and [tex]\mathrm dg=ue^{-u^2}\,\mathrm du[/tex], [tex]g=-\dfrac12e^{-u^2}[/tex] yields

[tex]\displaystyle2\int_0^\infty u^2e^{-u^2}\,\mathrm du=2\left(-\dfrac12ue^{-u^2}\bigg|_{u=0}^{u\to\infty}+\dfrac12\int_0^\infty e^{-u^2}\,\mathrm du\right)=\int_0^\infty e^{-u^2}\,\mathrm du[/tex]

You might already know that the value of this integral is [tex]\dfrac{\sqrt\pi}2[/tex], so you're done. Or, if you're not familiar, you can derive this result.

If [tex]\mathcal I(x)=\displaystyle\int_0^\infty e^{-x^2}\,\mathrm dx[/tex], then you have

[tex]\displaystyle\mathcal I(x)\mathcal I(y)=\left(\int_0^\infty e^{-x^2}\,\mathrm dx\right)\left(\int_0^\infty e^{-y^2}\,\mathrm dy\right)=\int_0^\infty\int_0^\infty e^{-(x^2+y^2)}\,\mathrm dx\,\mathrm dy[/tex]

Converting to polar coordinates yields

[tex]\displaystyle\int_0^{\pi/2}\int_0^\infty re^{-r^2}\,\mathrm dr\,\mathrm d\theta=\dfrac\pi2\int_0^\infty re^{-r^2}\,\mathrm dr=\dfrac\pi4[/tex]

and so

[tex]\displaystyle\mathcal I(x)^2=\mathcal I(x)\mathcal I(x)=\dfrac\pi4\implies \mathcal I(x)=\dfrac{\sqrt\pi}2[/tex]